Ancestry of the mammalian preplate and its derivatives: evolutionary relicts or embryonic adaptations? - Aboitiz, F; Montiel, J; García, R (2005)
Mammalian cortical development is preceded by the elaboration of a transient preplate, which is split into a superficial marginal zone and a deep subplate after the arrival of the cortical plate. There has been some controversy in the evolutionary interpretation of this transient structure, as some propose it to represent the ancestral cortex or pallium of non-mammals, while others consider it to be a phylogenetic novelty. The preplate and its derivatives contain components derived by both tangential and radial migration. Tangentially migrating elements include pioneer neurons and interneurons, both of subpallial origin, and Cajal-Retzius cells, mostly of pallial origin. Pioneer neurons were probably present in the ancestors of mammals, but may have changed their original superficial position to one below the developing cortex, thus attracting thalamic afferents in the subcortical white matter, and making them penetrate the cortex radially. In mammals, Cajal-Retzius cells appear to have increased both in number and on their level of reelin expression, perhaps in the context of controlling the final stages of migration in a radially expanding neoocortex. Radial-migrating cells are partly represented by the pyramidal-like cells of the subplate. These neurons resemble the excitatory elements of the adult reptilian cortex, but is not clear whether they are their true homologues. One possibility is that these cells appeared by virtue of a heterochronic process in which the earliest radial elements of the cortical plate began to be produced at progressively earlier developmental stages. Thus, we conclude that the mammalian preplate and its derivatives contain both ancestral and derived elements, all of which have been modified in the course of mammalian evolution to support an increasingly complex cortical plate development.